Determining braking power to recover energy in electric vehicle - ساميز عبد الله (Latakia University Journal -Engineering Sciences Series, 2020)
Recovering braking power is one of the most important topics in electric vehicles because it helps to increase the operating time of the vehicle by restoring part of the mechanical energy during braking to electrical energy. The aim of this study is to analyzing the power of the resulting forces during braking, the associated attenuation and the kinetic energy that can be utilized. Therefore, these results are applied to a model in Matlab environment to simulate the various slowdowns (the speed at which the braking starts and the deceleration rate), and how this is reflected on the required braking power and whether motor’s power is sufficient to receive all braking energy or do we need traditional braking (friction braking) as well.